2005
DOI: 10.4049/jimmunol.174.5.2476
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Priming of CTL by Transcutaneous Peptide Immunization with Imiquimod

Abstract: CTL are important in combating cancer and viruses. Therefore, triggering the complete potential of CTL effector functions by new vaccination strategies will not only improve prophylaxis of tumor or virus-related diseases, but also open opportunities for effective therapeutic immunizations. Using transcutaneous immunization, we show that epicutaneous (e.c.)4 application of an ointment containing a CTL epitope and the TLR7 ligand imiquimod is highly effective in activating T cells in mice using TCR-transgenic CT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
127
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(135 citation statements)
references
References 27 publications
6
127
1
1
Order By: Relevance
“…Epicutaneous or transmucosal immunization with protein and peptides has been reported to be efficient in inducing IFN-␥ production and cytotoxicity in T cells (38), especially when combined with inflammatory stimuli like tape stripping, cholera toxin, and Toll-like receptor ligands, such as oligonucleotides and imiquimod (16)(17)(18)(19). Seo et al (16) showed that LCs from tape-stripped skin are activated and express higher levels of costimulatory molecules and MHC-class I.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Epicutaneous or transmucosal immunization with protein and peptides has been reported to be efficient in inducing IFN-␥ production and cytotoxicity in T cells (38), especially when combined with inflammatory stimuli like tape stripping, cholera toxin, and Toll-like receptor ligands, such as oligonucleotides and imiquimod (16)(17)(18)(19). Seo et al (16) showed that LCs from tape-stripped skin are activated and express higher levels of costimulatory molecules and MHC-class I.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent reports showed that epicutaneous immunization with an MHC-class I-restricted peptide or with ovalbumin protein onto tape-stripped skin induces cytotoxic T cell activity in the draining lymph node which can be further increased by coadministration of cholera toxin (16,17). Others reported that these responses can also be boosted with Toll-like receptor ligands, such as oligonucleotides and imiquimod (18,19). Thus, epicutaneous immunization elicits T cell responses in the draining lymph nodes, but inflammation in the skin is necessary for an optimal response.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Based primarily on in vitro studies, it is envisaged that LCs undergo a process of maturation coordinate with migration, where they upregulate MHC, costimulatory, and adhesion molecules, and act as potent stimulators of naive CD4 and CD8 T cells when they arrive in the lymph node (3)(4)(5). Indeed, epicutaneous immunization strategies, which are presumed to involve LC, are effective at inducing functional CTL (6,7) and have led to clinical trials with positive preliminary findings for influenza and travelers' diarrhea (www.iomai.com) (8,9).…”
mentioning
confidence: 99%
“…Indeed, it was shown that topically applied antigen induced CD4 + and CD8 + T cell responses in the skindraining lymph nodes, most probably through presentation by migratory skin dendritic cells [36,62]. In several studies peptides or protein antigens were applied either onto barrier-disrupted skin [46] which is achieved by repeated application of adhesive tape onto the skin [20], or on untreated skin in combination with adjuvants like cholera toxin or TLR ligands [22,25,39]. We reported recently that protein antigen applied onto tape stripped skin induced proliferation of CD4 + and CD8 + T cells and development of long-lasting cytotoxic T cells.…”
Section: Strategies For Immunizing Cancer Patients Through Resident Dmentioning
confidence: 99%